Plant community and structural pattern analyses of Abraham Sacred Forest in Amhara Regional State, northwest Ethiopia. - Getinet Masresha Kassa; Ayenew Lisanu Teka; Getahun Tassew Melese (PLoS ONE)
Owing to its topographic variations, Ethiopia is a biodiversity-rich country. However, the long-term degradation of resources has resulted in isolated forest patches largely around sacred places. Thus, this work was aimed to evaluate the plant community formation and structural dynamics of the Abraham Sacred Forest patch. Data were collected from 60 plots located on transect lines. Five subplots (4 m2), four at each corner and center, were set to collect juveniles' data. Individuals of each species and cover abundance were recorded, and adults' stem girth was measured. Hierarchical cluster analysis was used to identify plant communities. A Kruskal-Wallis followed by Tukey's honestly significant difference test was performed to check the statistical significance among the plant communities. Shannon-Wiener diversity index, equitability index, and non-parametric species richness estimators were used to quantify species diversity, evenness, and richness, respectively. Structural parameters and size class ratios were used to analyze the vegetation structure and regeneration status. Seventy wood species, distributed in 62 genera and 38 families, were recorded. Fabaceae was the most species-rich (10 species) family. Three plant communities were identified. A Kruskal-Wallis test indicated that the community types showed significant differences (P < 0.05) with respect to altitude and slope. The density and basal area of the forest were 4580.4 ha-1 and 35.18 m2ha-1 respectively. The inverted J-shaped pattern in DBH classes implies a good reproduction status. However, importance value index and regeneration status analyses revealed that certain species, like Astropanax abyssinicum (Hochst. ex. A. Rich) Seem, Myrica salicifolia Hochst. ex. A. Rich and Dombeya torrida (G.F.Gmel) Bamps, require conservation priority.